Effects of Root Zone Warming on Maize Seedling Growth and Photosynthetic Characteristics Under Different Phosphorus Levels - Xia, Zhenqing; Zhang, Shibo; Wang, Qi; Zhang, Guixin; Fu, Yafang; Lu, Haidong (Frontiers in Plant Science, 2021)
Phosphorus content and root zone temperature are two major environmental factors affecting maize growth. Both low phosphorus and root zone high temperature stress can significantly affect the growth of maize, but the comprehensive effects of phosphorus deficiency and root zone warming are less studied. This study aimed to explore the effects of phosphorus deficiency and root zone warming on the root absorption capacity, total phosphorus content and photosynthetic fluorescence parameters of maize seedlings. The results showed that phosphorus deficiency and root zone warming significantly affected the growth of maize seedlings. Properly increasing the root zone temperature was beneficial to the growth of maize seedlings, but when the root zone temperature was too high, it can significantly affect the root and shoot development of maize seedlings. Maize shoots and roots had different responses to root zone warming and phosphorus deficiency. The root zone warming had a more significant impact on the root system, while phosphorus deficiency had a greater impact on the shoots. Phosphorus content and root zone warming had a strong interaction. Under the comprehensive influence of normal phosphorus supply and medium temperature in the root zone, the growth of maize seedlings was the best. The better root absorption function and vitality level of the root zone at moderate temperature conditions improved the absorption and utilization efficiency of phosphate fertilizer. Under the combined effects of low phosphorus and high temperature in the root zone, the growth was the worst. Under the condition of low-phosphorus, too high root zone temperature reduced root vitality, plant phosphorus content, which in turn affected plant growth and light energy utilization efficiency. In the management of corn production, when the supply of phosphate fertilizer is sufficient, the root zone temperature can be appropriately increased to give full play to the coupling effect of root zone temperature and phosphorus, and increase the plant's phosphorus absorption and utilization efficiency. While when the temperature in the root zone is too high, the effect of applying phosphate fertilizer is relatively poor. The soil cooling measures can be used to increase the absorption and utilization of phosphorus.